INCIDENCE OF IN-HOSPITAL GASTROINTESTINAL BLEEDING IN ST- SEGMENT ELEVATION MYOCARDIAL INFARCTION (STEMI) & NSTEMI PATIENTS, UNDERGOING PERCUTANEOUS CORONARY INTERVENTION (The Research of Medical Science Review, 2025)
OBJECTIVE: To determine the frequency of in-hospital gastrointestinal bleeding in ST-segment Elevation Myocardial Infarction (STEMI) and NSTEMI patients, undergoing percutaneous coronary intervention. METHODOLOGY: This descriptive cross-sectional research is scheduled for execution in 2024 within the Adult Cardiology Department of National Institute of Cardiovascular Diseases, Karachi, with an enrollment of 247 patients diagnosed with ST-segment elevation myocardial infarction (STEMI) who underwent primary percutaneous coronary intervention (PCI) within 24 hours of symptom onset. Eligible participants, aged between 45 and 70 years, irrespective of gender, will be incorporated for the objective of assessing the primary outcome. The dataset shall undergo meticulous analysis employing SPSS version 26, which will integrate both descriptive statistical techniques and the Chi-square test for thorough evaluation. RESULTS: Among a cohort of 247 patients undergoing percutaneous coronary intervention (PCI), the average age was recorded at 62.17 ± 7.68 years, with 181 individuals (73.3%) identified as male. A diagnosis of ST-elevation myocardial infarction (STEMI) was established in 185 patients (74.9%), whereas non-ST- elevation myocardial infarction (NSTEMI) was diagnosed in 62 patients (25.1%). The incidence of gastrointestinal bleeding was observed in 20 patients (8.09%), with 14 (70%) originating from the STEMI cohort and 6 (30%) from the NSTEMI cohort. Gastrointestinal bleeding (GIB) demonstrated a significant correlation with cardiogenic shock (25.0%, p=0.0001), the necessity for circulatory support (20.0%, p=0.002), and mortality rates (25.0%, p=0.0001). CONCLUSION: This study highlights that gastrointestinal hemorrhage represents a considerable in-hospital complication for patients diagnosed with ST- Elevation Myocardial Infarction (STEMI) and Non-ST-Elevation Myocardial Infarction (NSTEMI) who undergo percutaneous coronary intervention. The findings emphasize the clinical significance of identifying individuals at heightened risk, particularly those demonstrating hemodynamic instability, to enable the execution of timely preventative measures. Enhanced risk stratification and proactive management are essential to alleviate gastrointestinal complications and improve short-term clinical outcomes within this patient population.